RIGOROUS, A HOMEOPATHIC MEDICINE, EFFECTIVE FOR CONTROLLING APHIDS IN BREAD WHEAT - M. S. Wains; M. A. Ali; I. H. Waris; J. Anwar; M. Zulkiffal; W. Sabir; A. Rehman; M. Hussain; K. Miraj (Journal of Animal and Plant Sciences, 2010)
Rigorous is a homoeopathic and natural product, which was designed to control the wheat Aphid and enhance the production of wheat. The cultivar SEHER-06 was grown in 5 districts of Punjab in Randomized Complete Block Design with three replications to evaluate this medicine against aphids in wheat. Four different treatments of Rigorous were applied and represented as T1-T4. Post treatment data for aphid population/tiller and percent mortality as compared to pre-treatment data were taken at different time points (after 24, 72 hours and 7 days). The results revealed that treatment-2 (T2) (Rigorous 1.5% solution @ 1.5 litre + 100 litre of water/acre) revealed minimum aphid population and maximum aphid mortality percentage for all time points. The results showed that aphid population decreased and the mortality rate increased with the passage of time from 24 hour to 7 days. The treatment, T3 (water only) was the least detrimental for the coccinellids predator for all time points. There was a positive correlation between aphid population per tiller and number of coccinellids per plant for all durations. Rigorous application resulted in significant increase in grain yield per hectare as compared to control. The results concluded that Rigorous could be efficiently utilized for controlling aphids in bread wheat in addition to less detrimental effects to the natural enemies of aphids.
Keywords: Rigorous; wheat; aphids; coccinellids; grain yield